Press Statement: The Sudanese Parties to the Comprehensive Peace Agreement (CPA) held a Special Session on Post-Referendum Security Arrangements in Ethiopia (Tufts Archival Research Center, 2005)
This is a press statement by the African Union in regard to negotiations between the Sudanese government and Sudan People's Liberation movement facilitated by the African Union and pertains to the security zone, extension of the United Nations Mission in Sudan, forces in Southern Kordofan and Blue Nile, and Southerners associated with Sudan's Armed Forces.